2014
DOI: 10.1002/j.1532-2149.2014.490.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal responses and memory recall in migraineurs and headache‐free controls

Abstract: The findings suggest that in migraine, not only pain-related but also negative emotional words may act as triggers. These outcomes may have therapeutic implications as interventions could target problematic pain-related memories that influence migraine pain perception and pain-related physiological responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Similarly to our study, where there was a stronger group difference in subjective measures (stress levels) than objective measures, Tome-Pires et al found only a trend for higher skin conductance responses for pain descriptors and emotional words in migraine patients compared to controls, but a higher recall of emotional words in the migraine group [ 20 ].…”
Section: Discussionsupporting
confidence: 83%
“…Similarly to our study, where there was a stronger group difference in subjective measures (stress levels) than objective measures, Tome-Pires et al found only a trend for higher skin conductance responses for pain descriptors and emotional words in migraine patients compared to controls, but a higher recall of emotional words in the migraine group [ 20 ].…”
Section: Discussionsupporting
confidence: 83%
“…37,43,56 No significant difference was found regarding the proportion of pain words recalled (relative to neutral words) between the headache and control groups, although a small to medium effect size was indicated (k = 3, g = 0.438, 95% CI [−0.042, 0.918] P = 0.074). Despite no significant heterogeneity (Q = 4.707, P = 0.095), it is worth noting that 2 of the 3 studies reported significant memory bias towards pain information among those with chronic headaches 43 or chronic migraines, 56 yielding medium and large effect sizes, respectively. On the other hand, the results from the third study 37 produced no significant findings.…”
Section: Resultsmentioning
confidence: 95%
“…Skin conductance has also been used for the evaluation of pain in patients with fibromyalgia [188][189][190], showing a response above the base line [191,192], and also for the evaluation of pain in patients with chronic pain in the back [193][194][195][196][197][198] or with a high risk of chronic back pain [197], for the evaluation of shoulder pain [199], chronic lumbar pain [200], patients with post-trauma stress disorders [201], higher depressive disorder [202], tensional headache [195,203], migraine [204], irritable intestine syndrome [205], or arthritis [196]. The authors of [206] quantified the response to pain in patients with Rett syndrome by measuring skin conductance.…”
Section: Skin Conductance and Chronic Painmentioning
confidence: 99%